Emptiness as Transparency in the Late Poetry of Thomas Merton - Doud, Robert Eugene (Horizons, 1994)
This article examines chiefly Buddhist influences in Thomas Merton. Cables to the Ace is a book based on the Buddhist idea of pratitya-samutpada, or dependent co-origination. Beneath everything there is a blissful emptiness, or shunyata. The ace is the poet's selfhood at the point vierge, here interpreted as a Buddhist no-self. Heidegger's Gelassenheit also defines the point vierge. In The Geography of Lograire, a supreme karuna, or compassion, is poured out for all the countries and peoples of the world. Footprints of the Buddha figure in, and so does the transparency which is also emptiness.